2004
DOI: 10.1021/pr049906k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metabolic Labeling for Comparative Proteomics in Breast Cancer Cells

Abstract: Protein expression patterns in the cytosol of MCF-7 cells resistant to adriamycin and to adriamycin/verapamil were compared to that of the parental MCF-7 cell line and to each other using metabolic labeling and two-dimensional gel electrophoresis. Growing the parental MCF-7 cell line in 13C6-arginine- and 13C6-lysine-enriched medium resulted in C-terminal labeling of all tryptic peptides. The culture media was optimized for the incorporation of these labeled amino acids under conditions that also supported cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…SILAC has been used to provide both targeted (10,31) and more global quantitative analyses of cellular proteomes (20,25). We have documented the suitability of this approach using both primary SCs and immortalized S16 SCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SILAC has been used to provide both targeted (10,31) and more global quantitative analyses of cellular proteomes (20,25). We have documented the suitability of this approach using both primary SCs and immortalized S16 SCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of unlabeled amino acids in FCS can compete with the isotopically labeled amino acid and lead to a mixture of labeled and unlabeled amino-acyl tRNAs that both contribute to protein synthesis. Although the use of dFCS avoids this problem (9), some cells require low molecular weight serum components for growth that are also removed by dialysis (20). Because SILAC analysis has not been performed on primary or immortalized SCs, it was necessary to assess the ability of these cells to grow in dFCS and incorporate heavy amino acids into their proteomes.…”
Section: Silac As An Analytical Approach In Primary and Immortalized Scsmentioning
confidence: 99%
“…For quantitative PCR approaches, the use of certain reference genes such as GAPDH can also be problematic. It has been found that GAPDH expression was increased in the Adriamycin-resistant MCF7/Adr cells [46,47]. In a metabolic marker-focused proteomic profiling analysis of 101 breast cancer tissues, Isidoro et al [48] also found that the expression of GAPDH was significantly increased in patients with poor survival.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Proteomics studies reported so far have mainly been performed with breast cancer cell lines using either two-dimensional gel electrophoresis (11)(12)(13)(14) or LC-MS for protein separation (15)(16)(17). However, it is known that the proteomic makeup of a cultured cell is rather different from that of a tumor cell surrounded by its native microenvironment (18).…”
Section: Molecular and Cellular Proteomics 8:1278 -1294 2009mentioning
confidence: 99%